Towards a macroprudential surveillance and remedial policy formulation system for monitoring financial crisis - Biswa N. Bhattacharyay (Center for Economic Studies and ifo Institute (CESifo), 2009)
Several developing economies witnessed a large number of systemic financial and currency crises since the 1980s which resulted in severe economic, social, and political problems. The devastating impact of the 1982 and 1994-95 Mexican crises, the 1997-98 Asian financial crisis, the 1998 Russian crisis and the ongoing financial crisis of 2008-2009 suggest that maintaining financial sector stability through reduction of vulnerability is highly crucial. The world is now witnessing an unprecedented systemic financial crisis originated from USA in September 2008 together with a deep worldwide economic recession, particularly in developed countries of Europe and North America. This calls for devising and using on a regular basis an appropriate and effective monitoring and policy formulation system for detecting and addressing vulnerabilities leading to crisis. This paper proposes a macroprudential/financial soundness monitoring, analysis and remedial policy formulation system that can be used by most developing countries with or without crisis experience as well as developed countries with limited data. It also discusses a process for identifying, and compiling a set of leading macroprudential indicators/financial soundness indicators. An empirical illustration using Philippines data is presented.
Keywords: F30; E58; E44; G20; G10; G32; G28; 330; economic and financial vulnerability; macroprudential indicators and financial soundness indicators analysis; macroprudential surveillance and policy; developing countries; financial sector; currency and financial crises; Early Warning Models; Stress Test; Finanzmarktkrise; Frühwarnsystem; Finanzsektor; Makroökonomischer Einfluss; Wirtschaftsindikator; Staatliche Einflussnahme; Wirtschaftspolitik; Entwicklungsländer